Experimental study and mechanism analysis on bioeffects by nanosecond electromagnetic pulses - 王保义 杨杰斌 郭庆功 徐润民 刘长军 张弘 邹方东 王子淑 (Science China. Life sciences, 1997)
The athermal bioeffects caused by nanosecond electromagnetic pulses with body cells was studied by using a broad band transverse EM-wave cell (BTEM CELL). The experimental system and preliminary mechanism analysis were presented.